Pulsed Laser Acupuncture in the Treatment of Pain and Heart Rate Variability in Fibromyalgia Patients: A Pilot Randomized Clinical Trial: Pulsed Laser Acupuncture Apllied in Fibromyalgia - Almeida Boggiss, Érika; Coelho Rosário, Rhaynara; De lima, Rosana Aparecida; Silva, Paula Aparecida; Moreira, Rosa Maria; Da Silva, Karol Priscila; De farias, Caroline Lima; Dos Santos, Vanessa de Queiroz; Polaquini Simões, Rodrigo; Silva Santos, Adriana Teresa; et al. (Journal of Lasers in Medical Sciences, 2022)
Background: Laser acupuncture is a medically approved treatment for chronic pain, especially fibromyalgia. It is widely known that all pain is related to autonomic modulation, which may influence heart rate variability (HRV). There are robust studies in the literature on the effect of laser acupuncture with continuous frequency on musculoskeletal pain and autonomic modulation. However, little is known about the effect of pulsed frequency or individualized protocols. Therefore, the aim of this study was to evaluate the effect of pulsed laser acupuncture, applied in an individualized protocol, on pain intensity and HRV in patients with fibromyalgia. Methods: The study is characterized as a pilot randomized clinical controlled trial. The sample consisted of women with fibromyalgia between the ages of 40 and 80 years, who were randomized into two groups: a control group (CG; n = 10) and an experimental group (EG; n = 10). EG received the intervention twice a week for three weeks. Statistical analysis was calculated by delta (difference between post-intervention and pre-intervention) and the Shapiro–Wilk test (normality). For comparison between the groups, the Mann–Whitney test was used. Results: The results show a significant reduction in pain intensity as reported via the Pain Numerical Scale (PNS; p = 0.00), Generalized Pain Index (GPI; p = 0.00), and Symptom Severity Scale (SSS; p = 0.00). Conclusion: Pulsed laser acupuncture, when applied in an individualized protocol, can reduce pain intensity as reported on the PNS, GPI, and SSS. However, no therapeutic effect was observed for HRV.